Developing a growth mindset in education: a bibliometric analysis and its challenge during pandemic - Sugiarti Sugiarti; Arti Prihatini; Atika Permata Sari; Gamal Kusuma Zamahsari (Institute of Advanced Engineering and Science, 2024)
The growth mindset is essential for learning because students encounter numerous obstacles during the pandemic. However, only a few studies have examined research trends in growth mindset pedagogy. In filling this gap, this study aims to conduct a bibliometric study using the growth mindset pedagogy during the pandemic. Data from 81 Scopus-sourced scholarly articles on growth mindset in education from 2020–2022 was used. VOSviewer qualitatively analyzed the data. Results showed that the research cluster’s growth mindset is diverse and adaptive to learning dynamics, notably during the COVID-19 pandemic. Several research clusters examined instructors, students, and parents’ roles in learning. Another cluster focuses on academic achievement and teacher efforts to improve student performance. The research addresses student issues like depression, academic fatigue, and suicide ideation. Research on a growth mindset in education has grown quantitatively since 2021. Clusters 1, 2, and 4, 5 have the most research on active learning design to improve student academic performance and accomplishment through teachers and other supporting elements. Even though academic fatigue can lead to depression and suicidal ideation, research on academic achievement-related student issues is scarce. In conclusion, a growth mindset can significantly enhance academic performance and solve learning problems.